Neonatal stroke: Clinical characteristics and neurodevelopmental outcomes - Marwa M. Elgendy; Subhash Puthuraya; Carmela LoPiccolo; Wei Liu; Hany Aly; Sreenivas Karnati (Elsevier, 2022)
Background: Neonatal stroke can potentially result in significant neurological sequelae in affected infants. Studies on neurodevelopmental outcomes and the need for rehabilitation therapies in the first two years are limited. We aimed to describe the clinical characteristics, diagnostic evaluation, and neurodevelopmental outcomes of a cohort of infants with neonatal stroke. Methods: A retrospective cohort study of infants with neonatal stroke, from 2011 to 2020. Maternal and infant characteristics were described. Placental pathology, echocardiogram results, and prothrombotic evaluations were reported. The neurodevelopmental outcomes using Bayley scale of infant development (BSID III), rates of epilepsy and cerebral palsy, and the need for rehabilitation therapies at two years were described. Results: During the study period, 55 infants had neonatal stroke. Majority (93%) were term or late preterm infants. Maternal chorioamnionitis and perinatal HIE were diagnosed in about a third of the infants. Most (66%) of the infants presented with seizures. On brain MRI, the lesions were unilateral in 76% and arterial in origin in 86% of the infants. Meconium exposure (42%), intrauterine inflammation/infection (37%) and fetal vascular malperfusion (16%) were seen on placental histopathology. At two-year BSID III assessment, median (min, max) composite cognitive, language, and motor scores were 100 (55-145), 97 (47-124), and 100 (46-141), respectively. Among this cohort, epilepsy (27%), cerebral palsy (16%) and the need for rehabilitation therapies (physical −24%, occupational −18%, speech −21%) were reported at two years. Conclusion: Neonatal stroke presented commonly in term or late preterm infants with seizures. It was unilateral and arterial in origin in most infants. Maternal chorioamnionitis and perinatal HIE were the most commonly associated conditions at birth. About one-fifth of the infants had mild or severe developmental delays at two years. Epilepsy, cerebral palsy, and need for rehabilitation therapies were noted in a significant proportion of infants at two years.